The effects of 24 weeks of muay thai and bodybuilding training programs on lower limb performance, balance, and coordination - Bunyamin Haksever (Asociación Española de Ciencias del Deporte, 2021)
Objective: The aim of this study was to compare balance, coordination, and lower limb performance values between Muay Thai (MT) and bodybuilders (BB) training groups. Methods: A total of 35 (17 MT group and 18 BB group) participants were included in the study. MT and BB training programs were performed three sessions per week for 24 weeks. Lower limb performance, coordination static and dynamic balance were determined. Results: There was a significant difference between the MT and BB groups in terms of coordination (p=0.011) and non-dominant lower limb performance (p =0.038). However, the groups were similar in terms of static and dynamic balance. MT group had higher coordination and non-dominant lower limb performance values than BB group. However, there was no difference between the groups in terms of static/dynamic balance and the dominant lower limb performance. Conclusions: Therefore, balance, coordination and functional exercises should be added to training programs of BB and MT in order to improve performance.